Event-related potentials (ERPs) to schematic faces in adults and children - Henderson, Ross M.; McCulloch, Daphne L.; Herbert, Andrew M. (International journal of psychophysiology, 2003)
Event-related potentials (ERPs) were recorded from 4-year-old 8–10-year-old children and adults to a schematic face, inverted face and jumbled face. The subjects were instructed to fixate the stimuli and no other response was required. The schematic face and inverted face were shown with a frequency of 20% each and the remaining presentations (60%) were of the jumbled face. P1 and N170 peak latency were measurable in the children and adults. These peaks were at longer latencies in the children. P3 was measurable in the adults and 8–10-year-old children but not the 4-year-olds. The adults had larger and longer latency P1 and smaller amplitude N170 to the inverted face than the other faces. In contrast, the P1 was unaffected by inversion in the children and the N170 was not smaller to the inverted or jumbled face. It is concluded that this result reflects developmental differences in the processing of configuration, with the children relying on an under-specified configuration of the face.